Effets des sons anthropiques sur la faune marine Cas des projets éoliens offshore - Bonnel, Julien; Chauvaud, Sylvain; Chauvaud, Laurent; Mars, Jérôme (éditions Quae, 2022)
The development of offshore wind energy is currently under debate. The possible detrimental effects of noise pollution on marine life are a legitimate concern for civil society, industry and political bodies. This book, which brings together experts from various disciplines, reviews the scientific knowledge on the acoustic impact of offshore wind projects on marine fauna and the methods to reduce it. It is written in the context of the expected development of marine renewable energy (MRE) projects and focuses on the impact of noise from offshore works for the construction, operation and dismantling of offshore wind turbines on various compartments of marine fauna (marine mammals, fish, invertebrates, birds and turtles) This book is intended for impact study professionals, researchers, students, MRE industrialists, as well as territorial managers and members of nature protection associations.